An overview of exposure parameters, dose measurements and strategies for dose reduction in pediatric CT examinations. Issue 1 (14th February 2014) - Akhlaghi, P.; Miri Hakimabad, H.; Rafat Motavalli, L.
Abstract : CT scanning technology is a valuable tool to diagnose many diseases; however, the level of the radiation dose is a source of concern, especially for children. CT scan systems and dose measurement methods have evolved over the years; but reported pediatric effective doses (EDs) have sometimes exceeded the annual dose limit recommended by the ICRP (1 mSv per year for persons under 18 years) (ICRP, 2007a). Efforts have been made to reduce organ doses and EDs by adjusting the scan parameters. This paper describes the determinants of the ED, and the dose reduction techniques in pediatric imaging from the early age of CT examinations until now. The first epidemiological results regarding the associated risk of cancer are also briefly presented.